2021
DOI: 10.1039/d1gc90119b
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Flow-through solvolysis enables production of native-like lignin from biomass

Abstract: Correction for ‘Flow-through solvolysis enables production of native-like lignin from biomass’ by David G. Brandner et al., Green Chem., 2021, 23, 5437–5441, DOI: 10.1039/D1GC01591E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This study demonstrated better performances of flow when compared to batch processes in terms of product selectivity (> 80 %) using dioxane/water (9:1 (v/v) ratio) as solvent mixtures, Pd/C catalyst (Pd/C to Al 2 O 3 1:10 (w/w) ratio), reduction temperature of 463 K, H 2 flow of 20 cm 3 min -1 at 35-60 bar, educt flow of 0.2 cm 3 min -1 , and poplar wood as feedstock. In complementary work, a continuous-flow solvolytic extraction of lignin was coupled with batch, in situ, and ex situ flow RCF, revealing that flow systems enable the generation of native-like lignin structure utilizing MeOH at 498 K with 15 wt % of Ni/C and 30 bar of H 2 [126]. These two experiments demonstrated that flow systems are advantageous for the fundamental understanding of lignin depolymerization chemistry, providing distinct data for the catalytic and extraction steps.…”
Section: Lignin-first Via Reductive Catalytic Fractionationmentioning
confidence: 99%
“…This study demonstrated better performances of flow when compared to batch processes in terms of product selectivity (> 80 %) using dioxane/water (9:1 (v/v) ratio) as solvent mixtures, Pd/C catalyst (Pd/C to Al 2 O 3 1:10 (w/w) ratio), reduction temperature of 463 K, H 2 flow of 20 cm 3 min -1 at 35-60 bar, educt flow of 0.2 cm 3 min -1 , and poplar wood as feedstock. In complementary work, a continuous-flow solvolytic extraction of lignin was coupled with batch, in situ, and ex situ flow RCF, revealing that flow systems enable the generation of native-like lignin structure utilizing MeOH at 498 K with 15 wt % of Ni/C and 30 bar of H 2 [126]. These two experiments demonstrated that flow systems are advantageous for the fundamental understanding of lignin depolymerization chemistry, providing distinct data for the catalytic and extraction steps.…”
Section: Lignin-first Via Reductive Catalytic Fractionationmentioning
confidence: 99%